Effectiveness of Solar Disinfection (SODIS) in Improving the Microbial Quality of Well Water in Ago-Iwoye, Nigeria - Egberongbe, Haneefat Adebimpe; Uzodinma, Chukwuma Victor; Wahab, Kareem Ademola; Oluwatimileyin, Akinbola; Adekola, Hafeez Aderinsayo (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVE: To access safe drinking water remains a pressing challenge in many developing countries, where untreated groundwater serves as the primary household water source. METHODOLOGY: This study assessed the effectiveness of solar disinfection (SODIS) in improving the quality of well water in Ago-Iwoye, Ogun State, Nigeria. Water samples were collected from five locations and subjected to physicochemical and bacteriological analysis before and after solar exposure. RESULTS: Physicochemical results indicated that most parameters, including temperature (32.3 °C), turbidity (8.67 NTU), and biochemical oxygen demand (3.6 mg/L), exceeded World Health Organization (WHO) thresholds, suggesting compromised quality. Microbiological analysis revealed high baseline contamination, with microbial counts ranging from 50 × 10⁴ to 80 × 10⁴ cfu/mL. Following solar disinfection, counts were reduced to 15 × 10⁴–30 × 10⁴ cfu/mL, demonstrating a notable but incomplete reduction in microbial load. Morphological and biochemical characterization identified Pseudomonas spp. (38%), Klebsiella spp. (27%), Salmonella spp. (14%), Escherichia coli (11%) and Staphylococcus aureus (11%) as dominant isolates. Antimicrobial susceptibility testing revealed widespread resistance, particularly among Klebsiella and E. coli, while streptomycin and ampicillin remained the most effective drugs. CONCLUSION: Although SODIS significantly reduced microbial contamination, post-treatment levels remained above WHO guidelines, indicating that the method alone is insufficient to make well water potable. Findings highlight the need for combined low-cost purification strategies and regular monitoring to safeguard public health in rural Nigerian communities..